Group II complexes of N- and O-donors Mixed-ligands as anticancer agents. (15th November 2021) - Raza Shah, Syed; Shah, Zarbad; Khan, Ajmal; Yahya, Saira; Salman, Syed M.; Gul, Pasham; Flörke, Ulrich; yousuf, Samer; Anwar, Muhammad U.; Al-Harrasi, Ahmed
Graphical abstract: We report synthesis, characterization and anti-cancer activities of four new magnesium, calcium and strontium complexes containing 1, 10 – phenanthroline, p-amino benzoic acid and cinnamic acid. Abstract: Reactions of 1, 10-phenanthroline (phen ), p-amino benzoic acid (paba ) and cinnamic acid (cina ) with MCO3 (M = Mg, Ca, Sr) yielded two mononuclear magnesium complexes [{Mg(phen )(H2 O)4 }(phen )(paba )2 ] (1 ) and [{Mg(phen )(H2 O)4 }(phen )(cina )2 ] (2 ) and two one dimensional chains of both calcium and strontium [Ca(phen )(cina )]n (3 ), and [Sr(phen )(cina )]n (4 ) respectively. The structures were characterized by a variety of analytical techniques including IR, UV–Vis, 1 H NMR, elemental analysis, and single crystal X–ray diffraction analysis. In these complexes, phen binds via an N, Ń –chelate pocket, while the monoanionic paba — /cina — ligands either remains uncoordinated (in case of 1 and 2 ) or coordinated in a tridentate fashion (in case of 3 and 4 ). Complexes 1, 3 and 4 crystallize in the same orthorhombic space group Pbcn while complex 2 crystallizes in triclinic space group P 1. In complex 1 and 2, Mg 2+ cation adopts a distorted six-coordinate octahedral geometry comprising an [N2 O4] donor set while in complexes 3 and 4, Ca 2+ and Sr 2+ cations adopt a distorted eight-coordinate geometry comprising [N2O6] donor sets. Complexes 1, 2 and 4 were found to be potent anticancer against oral cancer cell line i.e. CAL-27 with IC50 1.85 ± 0.11, 2.98 ± 1.2 and 5.05 ± 0.35 respectively while complex 3 was inactive.